Toxicidade aguda e alterações hematológicas e renais do veneno da serpente Bothrops jararacussu em ratos - Bindá, Alexandre Havt (1999)
The most recent data from ophidian bites in Brazil show approximately an amount of 20.000 human accidents each year. This work has the objective of evaluating the acute toxicity and the hematological and renal alterations after experimental envenomation with the crude lyophilized venom of Bothrops jararacussu, in Wistar rats. Initially, we investigated the venom's acute toxicity and determinated its LD50. Four groups of six animais (n=24) were inoculated intraperitoneally with doses of 2, 4, 8 and 16 mg/kg. The LD50, after probit analyses, was 9,5 ± 0,44 mg/kg. As a complementary study, fragments of kidney, spleen, lungs, brain, liver and heart were collected for histopathological evaluation by Hematoxilin-Eosin staining under optic microscopy, from the dead and surviving animais. The last ones were sacrificed by cervical displacement after pentobarbital anesthesia (50mg/kg). All tissues presented congestion. The congestion was the only alteration observed in the liver and brain. We found dilatation of tubule cells, interstitial edema, proteic casts, and cellular exudation in the kidneys. The spleen presented white polp hyperplasia. The lungs presented cellular exudation and one case of bronchopneumonia. In one specific animal, the heart showed muscle destruction. The hematological evaluation was done with blood collection, preserved in heparin (500 Ul/ml), after intraperitoneally inoculation of the venom at the dose of 9,5mg/kg in eight groups of six animais (n=48). Each treated group had a control group, which were analyzed in the periods of 2, 6, 12 and 24 hours. When the treated and control groups were compared, an increase in the number of leukocytes, lymphocytes, monocytes, eosinophils, neutrophils was found, as well as in the mean corpuscular values MCV= mean corpuscular volume; MCHC= mean corpuscular hemoglobin concentration; and MCH= mean corpuscular hemoglobin. A decrease in the number of erythrocytes, in hemoglobin concentration, hematocrit, platelets and total plasma proteins (TPP) was also found. The isolated perfused rat kidney method was used to investigate the renal alterations. After intraperitoneally pentobarbitone anesthesia (50mg/kg) the right renal artery was cannulated through the upper mesenteric artery without blood flow interruption (Bowman, R.H., Maack, T.E. Amer. J. Physiol. 226: 426-430, 1974). Following 20 minutes for complete adjustments for both kidney and system, the experiments were started and lasted 120 minutes. The fírst 30 minutes were used as internai control. The venom was added in the system after these 30 minutes in the concentrations of 3, 10 and 30p.g/ml. Every ten minutes, urine and perfusate were collected for further laboratorial analysis of sodium, potassium, chloride, inulin and osmolarity. ANOVA comparisons were done for all groups. Fragments from treated and control kidneys were evaluated by Hematoxilin-Eosin staining under optic microscopy. The perfused pression (PP), renal vascular resistance (RVR), tubular sodium transport percentage (%TNa~), tubular chloride transport percentage (%TC1‘) were statistically different from control at 90 and 120 minutes in all venom concentrations. The proximal tubular sodium transport percentage (%pTNa+) and proximal tubular chloride transport percentage (%pTCF) decreased at 120 minutes in all concentrations; however, for the 30pg group the reduction started at 90 minutes. Tubular potassium transport percentage (%TK~) and proximal tubular potassium transport percentage (%pTK") reduced at 60 minutes in the groups of 10 and 30pg and at 120 minutes in all concentrations. The glomerular filtration rate (GFR) initially reduced at 60 minutes in the groups of 10 and 30pg, but increased at 120 minute in the group of 30pg. An increase at 120 minutes was also seen for urinary flow (UF), sodium, potassium, chloride excretion (ENa~, EK+, ECL') and osmotic clearance (Cosm) in the groups of 10 and 30pg. Complete dose-dependency was observed for renal vascular resistance (RVR), urinary flow (UF), and sodium, potassium, chloride excretion (ENa”, EK\ ECL') and osmotic clearance (Cosm) at 120 minutes.